2022
DOI: 10.3390/cells11050758
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Centriolar Composition Correlates with Internal Fertilization in Fish

Abstract: The sperm competition theory, as proposed by Geoff Parker, predicts that sperm evolve through a cascade of changes. As an example, internal fertilization is followed by sperm morphology diversification. However, little is known about the evolution of internal sperm structures. The centriole has an ancient and evolutionarily conserved canonical structure with signature 9-fold, radially symmetric microtubules that form the cell’s centrosomes, cilia, and flagella. Most animal spermatozoa have two centrioles, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…The fan-shaped, atypical distal centriole was discovered in 2018 using advanced electron microscopy 63 ; prior to this year, studies of spermatozoa mainly addressed the presence or lack of barrel-shaped centrioles. Two barrel-shaped, proximal and distal centrioles are found in the spermatozoa of most basal vertebrate external fertilizers 37 . In contrast, classic transmission electron microscopy (TEM) studies in mammalian spermatozoa found only one barrel-shaped centriole–the proximal centriole–with a few exceptions in marsupial and some rodent species that appear to lack it (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fan-shaped, atypical distal centriole was discovered in 2018 using advanced electron microscopy 63 ; prior to this year, studies of spermatozoa mainly addressed the presence or lack of barrel-shaped centrioles. Two barrel-shaped, proximal and distal centrioles are found in the spermatozoa of most basal vertebrate external fertilizers 37 . In contrast, classic transmission electron microscopy (TEM) studies in mammalian spermatozoa found only one barrel-shaped centriole–the proximal centriole–with a few exceptions in marsupial and some rodent species that appear to lack it (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Stage 2, the mammalian centriolar configuration, sperm competition within the female reproductive tract of internal fertilizers selected for sperm with atypical centrioles. This suggests that atypical centrioles are an innovation associated with changes in the mode of fertilization 37 39 , since internal fertilization provides unique challenges to the sperm. For example, in mammals, sperm swim in a multi-compartmentalized female reproductive tract with varying viscoelastic mucus and complex landscapes, including microgrooves 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The fan-shaped, atypical distal centriole was discovered in 2018 using advanced electron microscopy (Fishman et al, 2018); therefore, studies of spermatozoa prior to this year mainly addressed the presence or lack of barrel-shaped centrioles. Two barrel-shaped proximal and distal centrioles are found in the spermatozoa of most basal vertebrate external fertilizers (Turner et al, 2022). In contrast, classic transmission electron microscopy (TEM) studies in mammalian spermatozoa found only one barrel-shaped centriole, the proximal centriole, with a few exceptions in marsupial and some rodent species that appear to lack it ( Sfig 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…At this stage, the two centrioles are required for early embryogenesis (zygote to blastocyst), exhibiting centriole-dependent embryonic development (Yabe et al, 2007). Stage 2 – The mammalian centriolar configuration : sperm competition within the female reproductive tract of internal fertilizers selected for sperm with atypical centrioles, suggesting that atypical centrioles are an innovation associated with changes in the mode of fertilization (Fishman et al, 2017; Khire et al, 2016; Turner et al, 2022), as internal fertilization provides unique challenges to the sperm. For example, in mammals, sperm swim in a multi-compartmentalized female reproductive tract with varying viscoelastic mucus and complex landscapes, including microgrooves (reviewed in Tung and Suarez, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The DC is canonical in six distantly related fish clades, but the PC is either atypical or undetected ( Turner et al, 2017 ). While it is possible that these species lost their PC, another, more likely explanation is that the PC is modified to the point of being unrecognizable.…”
Section: Main Textmentioning
confidence: 99%